Rough picture fuzzy set and picture fuzzy topologies - Thảo, Nguyễn Xuân; Định, Nguyễn Văn (Journal of Computer Science and Cybernetics, 2015)
Approximation of a picture fuzzy set on a crisp approximation space gives a rough picture fuzzy set. In this paper, the concept of a rough picture set is introduced, besides, we also investigate some topological structures of a rough picture fuzzy set are investigated, such are lower and upper rough picture fuzzy approximation operators.